Personal, social and environmental predictors of daily fruit and vegetable intake in 11-year-old children in nine European countries. - Bourdeaudhuij, Ilse De (2008)
Objective: To investigate potential personal, social and physical environmental predictors of daily fruit intake and daily vegetable intake in 11-year-old boys and girls in nine European countries.Subjects: The total sample size was 13 305 (90.4% participation rate).Results: Overall, 43.2% of the children reported to eat fruit every day, 46.1% reported to eat vegetables every day. Daily fruit intake and daily vegetable intake was mainly associated with knowledge of the national recommendations, positive self-efficacy, positive liking and preference, parental modeling and demand and bringing fruit to school (odds ratio between 1.40 and 2.42, P<0.02). These factors were associated fairly consistently with daily fruit intake across all nine European countries, implying that a rather uniform intervention strategy to promote fruit can be used across Europe. For vegetables, the pattern was, however, less consistent. Differences between countries in cooking and preparing vegetables might be responsible for this larger diversity.Conclusions: This study showed that especially a combination of personal and social factors is related to daily fruit and vegetable intake in schoolchildren. This shows that a comprehensive multilevel intervention strategy based upon a series of individual and social correlates will be most promising in the promotion of daily fruit and vegetable intake in children.Keywords: health promotion, determinant, correlate, Pro children, fruit and vegetable consumption.